-4(3y)-5+3(5y+5)=

Simple and best practice solution for -4(3y)-5+3(5y+5)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(3y)-5+3(5y+5)= equation:


Simplifying
-4(3y) + -5 + 3(5y + 5) = 0

Remove parenthesis around (3y)
-4 * 3y + -5 + 3(5y + 5) = 0

Multiply -4 * 3
-12y + -5 + 3(5y + 5) = 0

Reorder the terms:
-12y + -5 + 3(5 + 5y) = 0
-12y + -5 + (5 * 3 + 5y * 3) = 0
-12y + -5 + (15 + 15y) = 0

Reorder the terms:
-5 + 15 + -12y + 15y = 0

Combine like terms: -5 + 15 = 10
10 + -12y + 15y = 0

Combine like terms: -12y + 15y = 3y
10 + 3y = 0

Solving
10 + 3y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-10' to each side of the equation.
10 + -10 + 3y = 0 + -10

Combine like terms: 10 + -10 = 0
0 + 3y = 0 + -10
3y = 0 + -10

Combine like terms: 0 + -10 = -10
3y = -10

Divide each side by '3'.
y = -3.333333333

Simplifying
y = -3.333333333

See similar equations:

| -7w+3(w+8)=16 | | 8-2y=-4y | | -97+12y+4=5(4y-3)-6 | | 12/2=6/x | | -19-4+28-35=-6-2m-5+3m | | 8/9(b-1/4)=2/3 | | -5(-5z)=150 | | 4n+3=86 | | -p+5(3p-2)+4= | | (5)(-2)+(5)(-2)(-3)= | | 20+-8x+30+-16x=180 | | -7r+6t-8s-r+12s+4t-t+2s-r= | | 6×12/2 | | -7x+4x+7+4x=(0-14)-(-8+5) | | 5-4(1-x)=21 | | 8x^2y^3z-2xyz+4x^3yz^2= | | -34(14x)+27(21x)=(75-75)+(-823+95) | | 2-x=-2(3x+4) | | 2X/3=3 | | 6x=(8-.25x)-(6-0.75x) | | (-4,3)M,=1/2 | | X/7=9=15 | | 2w=10+7w | | 3x^2-8xy+4y^2=6 | | 4x^2+378x-13631=0 | | 5+4h=9h | | 3(Mt+2)=7(4t+6) | | 50/6.25 | | 3x=(8-0.25x)-(3-.75x) | | 5/3*60 | | 2z+10=z | | 3(x+2)-4=2(4) |

Equations solver categories